Some notes on Campanula rotundifolia L. and documentation of phenotypic variation on three sites in northern lower Michigan. - Lehnen Jr. , Larry P. (1982)
http://deepblue.lib.umich.edu/bitstream/2027.42/53535/1/1970.pdf Description of 1970.pdf : Access restricted to on-site users at the U-M Biological Station.